Disentangling the influence of climate, soil and belowground microbes on local species richness in a dryland ecosystem of Northwest China - Jianming Wang; Ting Long; Yueming Zhong; Jingwen Li; Tianhan Zhang; Yiming Feng; Qi Lu (Scientific Reports, 2017)
Abstract Xinjiang Uygur Autonomous Region (XUAR) covers one of the largest drylands in the world, while the relative effects of different environmental factors on plant diversity are poorly understood. We sampled 66 sites in a typical dryland of XUAR, which covers more than 450,000 km2, to evaluate the relative influences of different factors on the patterns of local plant species richness (LPSR). We found that overall and herbaceous LPSR were positively correlated with water availability, soil nutrients but negatively correlated with energy availability, while the shrub LPSR showed the opposite response. Climate, soil attributes together explained 53.2% and 59.2% of the variance in overall and herbaceous LPSR, respectively; revealing that LPSR patterns were shaped by abiotic and underground biotic factors together. Only 31.5% of the variance in the shrub LPSR was explained by soil attributes, indicating that shrub LPSR was mainly limited by non-climatic factors. There findings provide robust evidence that relative contribution of climate and soil attributes differ markedly depending on the plant functional group. Furthermore, we found the different relationship between microbes and plant diversity, indicating that the linkages between soil microbial diversity and plant diversity may vary across functional groups of microbes and plant. These findings provide robust evidence that the relative roles of climate, soil and microbes differ markedly depending on the plant functional group. Microbial richness showed a significantly pure influence on the LPSR of all groups, suggesting that microbes play a non-negligible role in regulating plant diversity in dryland ecosystems.